WHAT TAXES DOES AN LLC SHOUD PAY? WHAT MANDATORY PAYMENTS IS A LIMITED LIABILITY COMPANY SUBJECT TO PER YEAR - Kazakov Firdavs Farxod ugli (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2024)
As soon as the process of official registration of the company’s activities is completed, the owner (or several) will have to decide on the tax system. Depending on it, the amount of mandatory regular payments, the schedule for depositing money and the specifics of accounting will be set. Therefore, it is necessary to figure out how much and what taxes an LLC pays. Since the financial burden on the company as a whole depends on the correctness of the choice.